2010
DOI: 10.1387/ijdb.082798ni
|View full text |Cite
|
Sign up to set email alerts
|

Placental metabolic reprogramming: do changes in the mix of energy-generating substrates modulate fetal growth?

Abstract: Insufficient oxygen leads to the cessation of growth in favor of cellular survival. Our unique model of high-altitude human pregnancy indicates that hypoxia-induced reductions in fetal growth occur at higher levels of oxygen than previously described. Fetal PO2 is surprisingly high and fetal oxygen consumption unaffected by high altitude, whereas fetal glucose delivery and consumption decrease. Placental delivery of energy-generating substrates to the fetus is thus altered by mild hypoxia, resulting in maintai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
54
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(60 citation statements)
references
References 121 publications
(140 reference statements)
6
54
0
Order By: Relevance
“…In the rat, glycaemia values are low at the foetal stage and increases before parturition [39]. The maternal-to-foetal glucose gradient varies significantly among species, being sharper in sheep and rats than in mice and humans [39][40][41][42][43]. Increased metabolic substrates in foetal circulation and increased foetal overgrowth have been previously addressed in human diabetic gestations and in different diabetes and pregnancy experimental models [3,4,10,44,45].…”
Section: Discussionmentioning
confidence: 99%
“…In the rat, glycaemia values are low at the foetal stage and increases before parturition [39]. The maternal-to-foetal glucose gradient varies significantly among species, being sharper in sheep and rats than in mice and humans [39][40][41][42][43]. Increased metabolic substrates in foetal circulation and increased foetal overgrowth have been previously addressed in human diabetic gestations and in different diabetes and pregnancy experimental models [3,4,10,44,45].…”
Section: Discussionmentioning
confidence: 99%
“…During isolated hypoxia induced at high altitude, for example, the human placenta decreases its consumption of oxygen and increases glycolysis to maintain its bioenergetic needs (Postigo et al 2009), and placental growth is not compromised. This results in the preservation of fetal O 2 delivery at the expense of glucose (Illsley et al 2010). Given that fetal hypoglycemia is strongly associated with fetal growth restriction, this results in impaired fetal growth.…”
Section: Placental Metabolismmentioning
confidence: 99%
“…Maternal partial pressure of O 2 in arterial blood (P a O 2 ) falls considerably at ≥2700 meters (m) elevation, and due to the sigmoid shape of the O 2 dissociation curve, P a O 2 falls precipitously at >3000 m. Even in pregnancies with entirely normal outcomes, physiologically lowered maternal P a O 2 results in a progressive slowing of the 3 rd -trimester fetal growth trajectory 220,221 This is despite significant placental adaptation both structurally (increased angiogenesis, decreased vascular syncytial membrane thickness) and metabolically. 222,223,224,225,226,227 Altitude studies in vivo showed that the human placenta subjected to hypoxic stress engages in a highly conserved process most obviously seen in solid tumors. 228,229,230,231 Metabolic reprogramming is a reversible form of hypometabolism in which an effective, largely mitochondrial driven switch from oxidative phosphorylation to aerobic (i.e.…”
Section: Potential Drug Targets Of Important Placental Pathways Imentioning
confidence: 99%